A comparative study of hierba buena and acetaminophen as analgesics for post-extraction pain - Domingo, Maria Bernardita L.
Hierba Buena is a herbal plant which has been found to possess analgesic properties. Herbolarios use this plant in treating a lot of other ailments like headache, backache, diarrhea, fever and dysmenorrhea. In this study, hierba buena was compared with acetaminophen, a commercial analgesic, to determine the efficacy of Hierba Buena for post-extraction pain. Placebo was used to minimize bias from the patients. Forty-six subjects of various ages and sexes, experiencing post-extraction pain were given a sealed envelope containing either Acetaminophen, Hierba Buena or placebo. The degree of pain relief experienced by each subject taking either Hierba Buena, Acetaminophen or placebo were recorded in the questionnaires provided for them. A double blind format of the evaluation was used in the study. Results indicate that: 1. Hierba Buena has an analgesic effect against post-extraction pain. 2. There is no significant difference between the efficacy of Hierba Buena and Acetaminophen. 3. Hierba Buena's onset of action approximate that of Acetaminophen.